An Analysis on Indonesian-English Abstract Translation by Google Translate - Herdawan, Deri (Universitas Islam Negeri Raden Intan Lampung, 2020)
Many international journals require authors to translate their articles into English, mostly the abstracts. The advancement of technology has paved the way to the invention of machine-translators, one of which is Google Translate. This research seeks to investigate (1) what translation method is currently used by Google Translate, and (2) what type of errors are committed by Google Translate in Indonesian-English abstract translation. A descriptive qualitative design was used in this research. Documents in the form of 15 abstracts (ca. 3500 words) were used in data analysis. The results showed that Google Translate implemented the literal translation method. In doing its translation, it committed several linguistic errors and many translation errors. Detailed results were presented and discussed in the coming sections, followed by recommendations for further research.